Phytoseiidae (Acari: Mesostigmata) on plants of the central region of the Brazilian cerrado - Rezende, José Marcos [UNESP]; Lofego, Antonio Carlos [UNESP] (Les Amis d'Acarologia, 2011)
Four surveys of Phytoseiidae species associated with native plants were conducted in ten fragments of Cerrado sensu stricto to determine the species associated with the plants of this region. Twelve of the most common plant species were sampled in each fragment. Twenty six phytoseiid species were recorded during the surveys. Stryphnodendron adstringens was the host plant that had the highest number of species (eight species). Amblyseius neochiapensis Lofego, Moraes and McMurtry 2000 and Neoseiulus tunus (De Leon) 1967 were the most common phytoseiid species. These species occurred on 24 and 20 host species, respectively. Approximately 76 % of the phytoseiids found belonged to the subfamily Amblyseiinae Muma, 1961. Almost 27 % of phytoseiid species recorded were associated with only one plant species. In addition, approximately two thirds of species found in this study also occur in the Atlantic Forest. The comparison of our results from the central areas with previous surveys in peripheral areas of the Cerrado showed that only 12 phytoseiid species were common to both areas.
Keywords: Brazil; Mites; Neotropic region; Phytoseiidae; Survey